2015
DOI: 10.1111/echo.12994
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Doppler of the Hepatic Veins in Noncardiac Diseases: What the Echocardiographer Should Know

Abstract: In most instances, the flow profile in the hepatic veins (HVs) reflects the fluctuation of pressure within the right atrium. Thus, interrogation of blood flow in the HVs is highly useful for the evaluation of right heart hemodynamics and has become an integral part of any routine echocardiographic examination. However, flow in the HVs is also affected by the state of the liver parenchyma and by the fluctuation of pressure within the thoracic cavity. Therefore, liver and pulmonary pathologies influence the flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Because hepatopathies modify the hepatic venous flow pattern, the results of our study provide a basis for future studies involving animals with changes that affect both the right side of the heart and the liver. More studies regarding hepatic venous flow pattern could help the ultrasonographer distinguish between diseases that cause hepatic congestion because of local disturbance or in response to right‐sided congestive heart failure.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Because hepatopathies modify the hepatic venous flow pattern, the results of our study provide a basis for future studies involving animals with changes that affect both the right side of the heart and the liver. More studies regarding hepatic venous flow pattern could help the ultrasonographer distinguish between diseases that cause hepatic congestion because of local disturbance or in response to right‐sided congestive heart failure.…”
Section: Discussionmentioning
confidence: 93%
“…In people, assessment of hepatic venous flow and its association with right heart hemodynamics is well established . This technique is uncommon in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the HV waveforms, it has been suggested that the significance of HV waveforms differ depending on the disease. 20,33 In patients with chronic liver disease, HV waveforms are useful for the estimation of liver fibrosis. [20][21][22][23] In patients with liver cirrhosis, the continuous HV waveform (namely C group in this study) is mainly caused by intrahepatic fat deposition, inflammatory or fibrotic changes, and changes in the compliance of the venous wall, suggesting the presence of severe liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, study population of this study was much larger than those of previous studies. 21,22,33,56 Second, although documented liver disease was excluded in this study, we could not fully exclude the presence of subsequent liver diseases, which may have affected the HV waveforms. Third, the relationships between HV waveforms and other estimations, such as liver biopsy, or other imaging, such as computed tomography and magnetic resonance imaging, were not examined in this study.…”
Section: Limitationsmentioning
confidence: 99%